Is it (dis)advantageous to have mixed parentage? Exploring education & work characteristics of children of interethnic unions in Britain - Raya Muttarak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2013)
Extant studies commonly claim that mixed ethnic children face difficulties in affiliating with either of the parental ethnic group, which consequently negatively affects their identity development. However, the majority of the existing literature is based on clinical evidence of small highly self-selected samples of those seeking psychological assistance. This paper aims to investigate the socioeconomic outcomes of mixed ethnic children using the Office for National Statistics Longitudinal Study data (N=35,302) which is a nationally representative 1% sample of the population in England and Wales. We hypothesise that an interethnic union between one immigrant parent and one parent from a majority population could promote integration of an offspring. Here educational attainment and employment status are used as indicators of socioeconomic integration. Logistic regression is employed to estimate the probabilities of having a degree qualification and being in employment of mixed ethnic individuals comparing to children of two ethnic minority parents and native children of two native white parents. Controlling for parental demographic and socio-economic characteristics as well as neighbourhood characteristics, the results suggest that having one native white parent bring children of immigrants closer to the characteristics of the majority population, signalling better integration of children with mixed parentage compared to their counterparts whose both parents are from minority ethnic group.
Keywords: 300; Mixed ethnic; interethnic union; integration; education; employment; ethnic minority; Ethnische Gruppe; Bevölkerungsstruktur; Soziale Integration; Bildungsniveau; Arbeitsmarktintegration; Großbritannien